Cracking the Catatonia: Plasma Exchange as Salvage Therapy in Refractory Neuropsychiatric Lupus - Kuruvilla Rohan; Bilal Hiba (Journal of Investigative Medicine High Impact Case Reports, 2026)
Neuropsychiatric systemic lupus erythematosus (NPSLE) is an uncommon but severe manifestation of systemic lupus with limited evidence to guide management when standard therapies fail. We report the case of a 19-year-old woman with new-onset SLE with myositis and nephritis overlap, positive for anti-Smith, anti-dsDNA, anti-PL7, and anti-Mi-2 antibodies with hypocomplementemia. Despite treatment with hydroxychloroquine and corticosteroids, she developed progressive weakness, catatonia and psychosis. MRI demonstrated diffuse cerebral volume loss. While hospitalized, she received IV methylprednisolone and mycophenolate mofetil, followed by cyclophosphamide, all with only transient improvement. Given her refractory disease, she underwent five sessions of therapeutic plasma exchange over eight days, which led to gradual resolution of catatonia and restoration of baseline mental and physical function without complications. This case underscores plasma exchange as a potential adjunctive therapy in severe, treatment-resistant NPSLE.